Refractory plasmonic nanocavities for chemistry at high temperatures - Naldoni, Alberto; Kudyshev, Zhaxylyk A.; Mascaretti, Luca; Kment, Štěpán; Boltasseva, Alexandra; Shalaev, Vladimir M.; Schmuki, Patrik; Zbořil, Radek (International Conference on Metamaterials, Photonic Crystals and Plasmonics, 2019)
Plasmonic metamaterials provide sub-wavelength light concentration and consequent localized heating, which holds great potential in the development of solar-thermal technologies. Here, I will present our recent efforts to fabricate large-scale refractory metamaterial films made by cylindrical plasmonic cavities of titanium nitride (TiN) and their use in various thermoplasmonic applications such as decomposition of molecules, synthesis of metal nanoparticles, conformal deposition of inorganic thin films, and steam generation.
CRIS-Team Scopus Importer:2024-12-16